Efficiency of speed and agilty dribbling of young basketball players - Jakovljevic, S.; Karalejic, M.; Ivanovic, J.; Strumbelj, E.; Erculj, F. (Kinesiologia Slovenica, 2017)
In the study we have measured and analyzed dribbling efficiency i.e. performance ratio (PR) of young basketball players. For this purpose five speed and agility tests (with and without the ball) were aplied on the group of 65 participants from two age groups (U16 and U18) and three players types groups (guards, forwards, centers). The results shows that guards performed the best in all tests with or without the ball, followed by forwards, while centers performed the worst. All player types achieve better results in tests without the ball, as dribbling the ball adds additional complexity to each test. The PR values are the smallest by the guards which means that basketball slow forwards and centers down more than guards. The older group players (U18) are on average better in all tests both with and without the ball. The PR is fairly consistent across all tests and there are no substantial differences between U18 and U16. We can conclude that ball dribbling has a substantial negative effect (slowdown) for speed and agility performance of heigher and less skilled players (forwards and especcilay centers), but not also for younger players.